Sex difference in attractiveness perceptions of strong and weak male walkers. Issue 6 (7th July 2016) - Fink, Bernhard; André, Selina; Mines, Johanna S.; Weege, Bettina; Shackelford, Todd K.; Butovskaya, Marina L.
Abstract: Objectives: Men and women accurately assess male physical strength from facial and body morphology cues. Women's assessments of male facial attractiveness, masculinity, and dominance correlate positively with male physical strength. A positive relationship also has been reported between physical strength and attractiveness of men's dance movements. Here, we investigate men's and women's attractiveness, dominance, and strength assessments from brief samples of male gait. Methods: Handgrip strength (HGS) was measured in 70 heterosexual men and their gait was motion‐captured. Men and women judged 20 precategorized strong (high HGS) and weak (low HGS) walkers on attractiveness, dominance, and strength, and provided a measure of their own HGS. Results: Both men and women judged strong walkers higher on dominance and strength than weak walkers. Women but not men judged strong walkers more attractive than weak walkers. These effects were independent of observers' physical strength. Conclusions: Male physical strength is conveyed not only through facial and body morphology, but also through body movements. We discuss our findings with reference to studies suggesting that physical strength provides information about male quality in contexts of inter‐ and intrasexual selection. Am. J. Hum. Biol. 28:913–917, 2016. © 2016Wiley Periodicals, Inc.